2017
DOI: 10.1016/j.jor.2017.07.013
|View full text |Cite
|
Sign up to set email alerts
|

Lateral column lengthening for adolescent idiopathic pes planovalgus deformity – Systematic review

Abstract: Pes planovalgus is the commonest foot deformity in children and presents with wide range of severity and symptoms. Surgery is mostly indicated for significant malalignment, resistant to non-surgical management. Lateral column lengthening is considered an appealing option as does not involve arthrodesis and allows for further growth and foot development. Methods: We conducted a systematic review on lateral column lengthening for pes planovalgus deformity in line with PRISMA-P Checklist. We carried out detailed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 21 publications
1
19
1
Order By: Relevance
“… 3 A 2017 review of lateral column lengthening performed on 156 paediatric flat feet (146 for idiopathic pes planus) found that the overall complication rate was 17.5% with a revision rate of 12.3%, most commonly for deformity recurrence. 56 Calcaneal osteotomies also are not without risk, with wound complications quoted as high as 28% and infection rates of 20%; although these have improved since minimally invasive techniques has become more popular. 57 …”
Section: Discussionmentioning
confidence: 99%
“… 3 A 2017 review of lateral column lengthening performed on 156 paediatric flat feet (146 for idiopathic pes planus) found that the overall complication rate was 17.5% with a revision rate of 12.3%, most commonly for deformity recurrence. 56 Calcaneal osteotomies also are not without risk, with wound complications quoted as high as 28% and infection rates of 20%; although these have improved since minimally invasive techniques has become more popular. 57 …”
Section: Discussionmentioning
confidence: 99%
“…Moraleda et al [ 26 ] also reported good clinical and radiographic results in a series of 21 children (33 feet) with symptomatic flexible flatfoot surgical treatment with a calcaneal lengthening osteotomy. More recently, Kumar and Sonanis [ 27 ] reported a systematic review on lateral column lengthening performed in adolescent pes planovalgus deformity. These authors identified seven studies with 103 patients involving 156 feet and concluded that lateral column lengthening leads to good clinical and radiological outcome with high patient satisfaction and acceptable complication rate.…”
Section: Discussionmentioning
confidence: 99%
“…It realigns the foot by lengthening the lateral column and allowing further bone growth. Lateral column lengthening in adolescents with pes planovalgus has good radiological and clinical outcomes, with high patient satisfaction [ 7 ]. Graft selection includes autologous iliac bone grafts (AIBG), allografts, and xenografts.…”
Section: Introductionmentioning
confidence: 99%